2012
DOI: 10.1637/10191-041012-reg.1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Holding Time on the Likelihood of Moving Internally Contaminated Eggs from a Highly Pathogenic Avian Influenza Infected but Undetected Commercial Table-Egg Layer Flock

Abstract: Emergency response during a highly pathogenic avian influenza (HPAI) outbreak may involve quarantine and movement controls for poultry products such as eggs. However, such disease control measures may disrupt business continuity and impact food security, since egg production facilities often do not have sufficient capacity to store eggs for prolonged periods. We propose the incorporation of a holding time before egg movement in conjunction with targeted active surveillance as a novel approach to move eggs from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…An opportunity to increase the application of dynamical models within the decision-making process is to focus on objective-driven models that provide practical predictions that are directly useful to those managing disease. Indeed, dynamic models have been used mechanistically for avian influenza (Malladi et al, 2012;Weaver et al, 2012;Bonney et al, 2018), brucellosis (Hobbs et al, 2015), and foot-and-mouth disease (Buhnerkempe et al, 2014;Roche et al, 2015) providing practical objectivedriven predictions to support disease management decisions. Recognizing that modeling is a means to improve disease management and outcomes is important and fosters increased use of these tools.…”
Section: Practical Challengesmentioning
confidence: 99%
“…An opportunity to increase the application of dynamical models within the decision-making process is to focus on objective-driven models that provide practical predictions that are directly useful to those managing disease. Indeed, dynamic models have been used mechanistically for avian influenza (Malladi et al, 2012;Weaver et al, 2012;Bonney et al, 2018), brucellosis (Hobbs et al, 2015), and foot-and-mouth disease (Buhnerkempe et al, 2014;Roche et al, 2015) providing practical objectivedriven predictions to support disease management decisions. Recognizing that modeling is a means to improve disease management and outcomes is important and fosters increased use of these tools.…”
Section: Practical Challengesmentioning
confidence: 99%
“…In the US, analyses have been performed to simulate the effect of incorporating a holding time before egg movement in conjunction with targeted active surveillance as a novel approach to move eggs from flocks within a control area with a low likelihood of them being contaminated with HPAI. Malladi et al (2012) used a stochastic disease transmission model to estimate the HPAI disease prevalence, mortality and fraction of internally contaminated eggs at various days after the infection of a layer flock. The outcome suggested a significant reduction in the number of internally contaminated eggs moved from an HPAI-infected but undetected flock with each additional day of holding time since the likelihood to detect the outbreak in the flock increases.…”
Section: International Trade and Intra-eu Transportmentioning
confidence: 99%
“…Malladi et al. () used a stochastic disease transmission model to estimate the HPAI disease prevalence, mortality and fraction of internally contaminated eggs at various days after the infection of a layer flock. The outcome suggested a significant reduction in the number of internally contaminated eggs moved from an HPAI‐infected but undetected flock with each additional day of holding time since the likelihood to detect the outbreak in the flock increases.…”
Section: Appendix F – Ai Introduction Non‐wild Bird Pathwaysmentioning
confidence: 99%
“…For an example of the latter, a within-flock model showed that vaccines conferring incomplete protection could counterintuitively increase the infectiousness of a flock, by delaying the time to detection and depopulation (Savill et al, 2006). Within-flock models have also been used to: (1) infer important events – such as the day of introduction – from mortality data (Bos et al, 2007), (2) estimate the risk of HPAIV transmission due to the movement of poultry-industry products from monitored flocks (i.e., flocks not known to be infected with HPAIV) into commerce (Malladi et al, 2012), (3) estimate important epidemiological parameters (Bouma et al, 2009) and (4) estimate mean time to detection for HPAIV strains under different surveillance-detection triggers (Weaver et al, 2012). …”
Section: Transmission Within Poultry Flocksmentioning
confidence: 99%